Profil pengalaman belajar siswa dalam menjelaskan fenomena ilmiah pada IPA/biologi selama penerapan pembelajaran daring di masa pandemi - Dewi Wansantika Gunawan; Tri Suwandi; Ana Ratna Wulan (Assimilation: Indonesian Journal of Biology Education, 2021)
This study aims to describe student's learning experiences in explaining scientific phenomena in online science/biology learning. This study uses a descriptive method, the data sources are questionnaires and Student Worksheets (LKS) from six schools in the city of Bandung which were selected by stratified random sampling with good, sufficient and poor categories based on the 2019 BSNP. There are 207 state junior high school students in Bandung City who filled out a 40-item questionnaire to answer this research. Questionnaire items for students have been adjusted to the skills to explain scientific phenomena based on the PISA 2018 framework. The results show that the student's learning experience in explaining scientific phenomena of Science/Biology when online learning has not been implemented optimally. The results show that the skill to explain scientific phenomena gets score 1,01. There are results of the worksheet’s analysis which show that the orders or questions on the worksheet that have been made by the teacher are 50% according to those obtained from schools in the good category. Through this research, the problem is that when doing practicum, the material is not understood because of the discrepancy of the material during the learning process.